Administration of fusion cytokines induces tumor regression and systemic antitumor immunity. Issue 2 (4th May 2021) - Zhang, Jinyu; Zhao, Xuan
Abstract: It is difficult to improve the curative effects of cancer immunotherapy on solid tumors. Cytokines, as powerful immune regulators, show potential in activating host antitumor immunity. We have previously found that the administration of certain cytokine combinations induces complete tumor clearance. Here, we constructed cognate fusion cytokines and evaluated their antitumor effects in various mouse tumor models. The in situ induction of the expression of the fusion cytokine IL12IL2GMCSF caused tumor eradication, including that of the tumors at advanced stages. An immune memory against unrelated syngeneic tumors was also elicited. Furthermore, flow cytometry analysis revealed that tumor‐infiltrating CD3+ cells were greatly increased in the treated tumors and were accompanied by an elevation of CD8+/CD4+ ratios. This fusion protein exhibited superior immune activating capability compared to that of cytokine mixtures, in the experiments done in vitro. We also induced tumor regression in various immunocompetent tumor models via intratumoral injection. To improve its translational potential for clinical application, a systemically‐administered immunocytokine, IL12IL2DiaNFGMCSF, was constructed by inserting a tumor‐targeting diabody in the fusion protein. This protein also displayed good immune stimulating activities in vitro. Intravenous infusion of IL12IL2DiaNFGMCSF induced tumor‐infiltrating immune cell alterations like IL12IL2GMCSF, with moderate serum IFNγ increment. Therapeutic effects were observed in the various tumor models after systemic administration of IL12IL2DiaNFGMCSF, but with slight toxicity. These results show the feasibility of developing a versatile cancer immunotherapy. Abstract : Here, we constructed cognate fusion cytokines and evaluated their antitumor effects in various mouse tumor models. The fusion cytokines can elicit antitumor immunity through synergistic effects on the immune cells. Administration of these proteins induced tumor regression in various tumor models with slight toxicity. These results show the feasibility of developing a versatile cancer immunotherapy.